An Environmental Sociology for the Anthropocene. (February 2017) - Bowden, Gary
Abstract : Attention to the relationship between nature and society has been a defining feature of environmental sociology since its inception. Early research, incorporating insights from ecology, argued for the need to (1) theorize the causal connections between nature and society and (2) contextualize those connections in terms of biophysical limits resulting from resource scarcity. Over the past two decades, partly in response to new forms of existential threat such as climate change, the treatment of nature and society as distinct entities has given way to a focus on socio‐natural assemblages. Using the Anthropocene as a lens to explore this emerging view, it is argued (1) that current theorizing on the socio‐natural assemblage needs to pay more attention to the issues of temporality and complexity, (2) that taking these factors into account reconceptualizes the nature‐society relationship as a complex, evolving socio‐natural assemblage, (3) that this evolutionary process needs to be understood in the context of cosmic evolution and the tension between entropy and the emergence of local complexity, and (4) that constraints on human development arise from the tension between these two tendencies, not from resource scarcity. An environmental sociology for the Anthropocene, one based on assumptions about the nature of causal dynamics and context consistent with our understanding of current earth system science, is proposed. L'attention portée à la relation entre la nature et la société a été un trait caractéristique de la sociologie de l'environnement depuis sa création. La recherche initiale, intégrant les connaissances de l'écologie, a soutenu la nécessité de (1) théoriser les liens causaux entre la nature et la société et (2) contextualiser ces connexions en termes de limites biophysiques résultant de la pénurie de ressources. Au cours des deux derniéres décennies, en partie en réponse à de nouvelles formes de menace existentielle telles que le changement climatique, le traitement de la nature et de la société en tant qu'entités distinctes a fait place à un accent sur les assemblages socio‐naturels. En utilisant l'anthropocéne comme une lentille pour explorer ce point de vue émergeant, on fait valoir (1) que la théorisation actuelle sur l'assemblage socio‐naturel doit accorder plus d'attention aux questions de temporalité et de complexité, (2) que prendre ces facteurs en compte reconceptualise la relation entre la nature et la société en tant qu'assemblage socio‐naturel complexe et en évolution, (3) que ce processus évolutif doit être compris dans le contexte de l'évolution cosmique et de la tension entre entropie et émergence de la complexité locale, et (4) sur le développement humain découlent de la tension entre ces deux tendances, et non de la pénurie de ressources. Une sociologie de l'environnement pour l'anthropocéne, fondée sur des hypothéses sur la nature de la dynamique causale et du contexte compatible avec notre compréhension de la science actuelle du systéme terrestre, est proposée.